Lost in translation: transformation in the first round of institutional audits - McKenna, Sioux; Quinn, Lynn (South African Journal of Higher Education, 2016)
The South African higher education institutional audit process was introduced alongside similar endeavors internationally. However, despite many similarities, each country foregrounds different concerns within their higher education quality processes. In their seminal article, Harvey and Green suggest five possible notions of quality, one of which is quality as transformation, and in South Africa the message has been clearly stated: notions of quality are intricately related to transformation. Local research has however suggested that the notion of ‘transformation’ as quality takes on particular nuances within this country’s context. In the two institutional case studies presented here, the ‘quality as transformation’ discourse appears to have been largely lost in translation. In one university transformation was not called upon to construct notions of quality; quality was primarily constructed by a discourse of excellence. In the other institution, the transformation aspects of quality seem to have been interpreted in a particularly reductionist way as relating solely to student racial demographics. In both cases, this paper argues that the ‘quality as transformation’ discourse prevalent in the audit documentation in the South African context was lost somewhere between the intentions embodied in national documents and the processes embarked upon by institutions.